2001
DOI: 10.1080/019262301316905282
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Toxicity and Recovery of Fischer 344 Rats Following Exposure to 2-Aminoanthracene by Intraperitoneal Injection

Abstract: Humans may be exposed to 2-aminoanthracen e (2-AA), a substituted polycyclic aromatic hydrocarbon , and a recognized mutagen and carcinogen , through oral and respiratory routes from contact with a variety of environmenta l sources. For the present study, we sought to evaluate hepatic damage and recovery in Fischer 344 rats following multiple IP injections of 5 mg of 2-AA. Rats were injected weekly for up to 5 weeks. Subgroups were then allowed to recover for 1, 5, or 9 weeks, and biochemical and pathologic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…TOXICOLOGIC PATHOLOGY rats that were subjected to DMBA exposure suffered from irreversible impairment in glycogen metabolism. Studies by others applying PAH to outbred rodents described dose-and duration-dependent liver pathology, as we also found in this study (Table 1), including foci of altered hepatocytes, such as hepatocyte hypertrophy, multinucleated hepatocytes, inflammation, pigmentation, necrosis, and highly increased incidence of hepatocellular adenoma (Baker et al 2001;Mishra et al 2009;NTP technical report 2006;Safer and Al-Nughamish 1999;Tsuda and Farber 1980). It has been suggested that possible mechanisms of hepatotoxicity include enhanced production of oxygenderived free radicals resulting in depletion in intracellular reduced glutathione (Bironaite and Ollinger 1997;Stadlbauer et al 2005).…”
Section: Discussionsupporting
confidence: 68%
“…TOXICOLOGIC PATHOLOGY rats that were subjected to DMBA exposure suffered from irreversible impairment in glycogen metabolism. Studies by others applying PAH to outbred rodents described dose-and duration-dependent liver pathology, as we also found in this study (Table 1), including foci of altered hepatocytes, such as hepatocyte hypertrophy, multinucleated hepatocytes, inflammation, pigmentation, necrosis, and highly increased incidence of hepatocellular adenoma (Baker et al 2001;Mishra et al 2009;NTP technical report 2006;Safer and Al-Nughamish 1999;Tsuda and Farber 1980). It has been suggested that possible mechanisms of hepatotoxicity include enhanced production of oxygenderived free radicals resulting in depletion in intracellular reduced glutathione (Bironaite and Ollinger 1997;Stadlbauer et al 2005).…”
Section: Discussionsupporting
confidence: 68%
“…In this study, 4-NQO produced the ultimate mutagenic compound, which bound to DNA and generated stable quinolone-purine mono adducts [1]. On the other hand, 2-AA preferred the biotransformation pathway, where a cytochrome P450-dependent monooxygenase produced a nitrene moiety that bound to DNA [2]. Natural products contain many substances that can likely reduce mutation and cancer.…”
Section: Discussionmentioning
confidence: 77%
“…For example, 4-nitroquinoline-N-oxide (4-NQO), a direct and strong mutagen, is a quinoline derivative carcinogen and can also induce potent intracellular production of oxidative stress [1]. In addition, 2aminoanthracene (2-AA), a known carcinogenic polycyclic aromatic amine, can induce tumors primarily in the liver [2]. In Ames test, 2-AA requires metabolic activation by the S9 liver preparation.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 4-NQO produced the ultimate mutagenic compound, which binds to DNA and generates stable quinoline-purine mono adducts (Arima et al, 2006). On the other hand, 2-AA prefers the biotransformation pathway, where a cytochrome P450-dependent monooxygenase produces a nitrene moiety that binds to DNA (Baker et al, 2001). Table 6 shows that WLT causes inhibition of the mutagenicity of 4-NQO and 2-AA, in the S. typhimurium bacterial model.…”
Section: Tablementioning
confidence: 90%
“…For example, 2-aminoanthracene (2-AA), a known carcinogenic polycyclic aromatic amine, can induce tumors primarily in the liver (Baker et al, 2001). However, 2-AA must submit to metabolic activation, in order to display its carcinogenicity.…”
Section: Introductionmentioning
confidence: 99%